Influence of School Principal Leadership and Quality Management Administration on the Performance of Teachers Through Work Motivation in Non-Formal Schools - Erwin Erlangga; Rini Sugiarti; Mulya Virgonita Iswandari Winta; Muhammad Abd Hadi Bunyamin; Deafika Trisnanda Riesta (Universitas Negeri Semarang, 2024)
Education in non-formal schools, particularly at the middle level requires special attention to enhance educational quality. School principal leadership and quality management administration have been recognized as key factors potentially affecting teacher performance. However, the relationship between these factors and teacher work motivation in non-formal schools is not fully understood. This study aims to investigate the relationship between school principal leadership, quality management administration, work motivation, and teacher performance in middle level non-formal schools. the study employs a survey method using questionnaires as the data collection instrument. The research sample consists of teachers from several non-formal schools selected randomly. Data analysis is conducted using descriptive statistical techniques and regression analysis. The analysis results indicate that school principal leadership positively influences teacher work motivation in non-formal schools. Quality management administration also has a positive effect on teacher work motivation. Furthermore, teacher work motivation significantly influences teacher performance in non-formal schools. This study concludes that school principal leadership and quality management administration positively affect teacher work motivation, which in turn influences teacher performance in non-formal schools. Therefore, the development of strategies to enhance school principal leadership, quality management administration, and teacher work motivation in non-formal schools will support the improvement of educational quality at this level. The main contribution of this research is to clarify the relationship between school principal leadership, quality management administration, work motivation, and teacher performance in non-formal schools, which can serve as a basis for the development of more effective educational policies and practices at this level